Characterization of cannabis varieties and the intrinsic and extrinsic factors affecting cannabis germination and seedling establishment: a descriptive review - Langa, Sabeliwe; Magwaza, Lembe Samukelo; Mditshwa, Asanda; Tesfay, Samson Zeray (Elsevier, 2023)
Cannabis sativa L. is the utmost consumed, grown, and produced illicit drug worldwide. The psychotropic activity of the component (-)-trans-∆9-tetrahydrocannabinol (∆9-THC), however, led to the banning of cannabis worldwide for many centuries. Besides being the most popular crop for recreational purposes, cannabis is grown globally as a multifunctional agricultural crop for its oily seeds and long, durable fibers. These properties have led to cannabis application in various industries, including agriculture, textile, bio-composite, papermaking, automotive, construction, and biofuel. Furthermore, medicinal cannabis constitutes of high concentration of cannabinoids, which have been discovered relevant in the pharmaceutical industry. As a result, various countries worldwide have relaxed regulations on cannabis. However, the cannabis products’ final use depends on the cultivar. Yet, the crop has hundreds of cultivars owing to constant breeding and human selection, which has altered the original plant with the spread of the crop worldwide. Generally, these cultivars possess chemical composition that varies genetically, and with the growing environmental conditions. Therefore, the current descriptive review of literature highlights the techniques available for classifying cannabis varieties, given the ongoing debate over classifying cultivars into distinct taxonomic groups. The effect of intrinsic and extrinsic factors on cannabis germination and seedling establishment are also highlighted.
Keywords: Cannabis; Environmental factors; Seed quality; Taxonomy; Reserve mobilization